Research on Basic Theory and Key Technology of Ultra-High-Speed, Ultra-Large-Capacity, Ultra-Long-Haul Optical Transmission - Shaohua Yu; Qi Yang; Daojun Xue; Zhixue He; Cai Li (Dianxin kexue)
Ultra-high-speed, ultra-large-capacity and ultra-long-haul（3U）optical transmission as a new mode of communication can greatly promote the next generation of optical internet and broadband mobile communication network development and technological progress, therefore 3U has become the focus of international high-tech intellectual property and competition ground. Starting from the background and significance of 3U research, the three scientific problems in 3U were given, and the architecture, basic theory and key technology of 3U optical transmission were introduced. Finally, the verification platform was introduced together with the important experiments completed on the platform, as well as the industrial application of the innovative achievements.